Implementasi Open Gl Untuk Pembuatan Objek 3d: Implementasi Open Gl Untuk Pembuatan Objek 3d - Muhammad Adnani; Achmad Zakki Falani (ZETROEM, 2021)
Computer Graphics is a part of computer science that deals with the creation and manipulation of (visual) images digitally. A simple form of computer graphics is 2D computer graphics which later evolved into 3D computer graphics, image-based (image processing), and pattern recognition (pattern recognition). Computer graphics are often also known as data visualization. Graphics include images and other imagery generated by the computer in the form of lines. OpenGL (Open Graphics Library) is an API standard that can be used to create graphics-based applications, both two-dimensional (2D) and three-dimensional (3D). OpenGL is cross-platform, meaning that it can be run on various operating system platforms that exist today. using OpenGL, we first need a conception of the interface in its implementation of object protection. One method that is commonly used is to create a window-based OpenGL. To be able to conceptualize windowing in OpenGL, we need a certain tool. What we are using this time is GLUT (OpenGL Utility Toolkit).